Buddhist Art in the Royal Funeral Pyre - ยิ่งยง พระปรรณพัชร์ (Journal of Buddhist Education and Research (JBER), 2024)
The importance of Buddhist art in the royal funeral pyre can be categorised into 3 aspects which are general science, social science, and humanities. Furthermore, the royal funeral pyre reflects om the significance of the Thai monarchy and the loyalty of civilians from every region towards their king. Moreover, the royal funeral pyre is highlighted as being mesmerising, fascinating and elegant in order to honour His Majesty. On the other hand, the pyre demonstrates the fact that nothing in this world will last forever. Despite of the magnificence of the pyre, it requires to be abolished into pieces like the fact that every human has to eventually die and only leave their great virtues and legacies behind for the next generation to learn and follow in their practice.